A Feminist Gaze: The Objectification of Women in Hamid’s The Prisoner - Naseem Ullah; Dr. Shaukat Ali (Corresponding Author); Anum Khan (`, 2025)
This study examines the objectification of women in The Prisoner by Omar Shahid Hamid through a qualitative, close-reading method. Textual references are interpreted using Nussbaum’s framework of objectification, including instrumentality, denial of autonomy, inertness, violability, fungibility, ownership, and denial of subjectivity. The analysis reveals that female characters are consistently treated as objects rather than individuals: Naika arranges girls for the police, ward boys reduce women to pleasure, Maqsood Mahr and the Home Minister assign them monetary value, Hassan Ali views them as interchangeable commodities, and both police officers and the brothel madam control their bodies. Salma Begum is depicted as a purchasable commodity, underscoring how women are traded like marketable objects. The study contributes a feminist interpretation by foregrounding women’s objectification in the novel and recommends that future research explore the intersection of gender, power, and urban violence in Hamid’s works. Key Words: Commodity, Feminism, Integrity, Object, Objectification, Subordination, Women.